Design and Testing of an X-Band Microstrip Patch Antenna for Microwave Breast Imaging - M., Lavanya; R., Karthika; M., Srigurupriya A.; C., Narmadha (IRO Journal on Sustainable Wireless Systems, 2025)
Breast cancer continues to be the leading cause of death in women, indicating the need for effective, non-destructive, and radiation-free imaging technology. Microwave imaging is an adequate instrument with the potential to differentiate between cancerous and normal tissue based on contrast in dielectric properties. The design, simulation, fabrication, and measurement of a 7.97 GHz X-band microstrip patch antenna for biomedical high-resolution applications of microwave breast imaging are presented in this paper. The antenna is fabricated on jean material with a thickness of 1 mm as a wearable flexible substrate for biomedical applications. The return loss value and VSWR, calculated with Ansys HFSS Student Edition, are -26.3 dB and nearly 1, indicating good impedance matching as well as a lack of signal reflection. Operation at high frequencies offers better spatial resolution for more precise tumor detection. The new antenna will be simulated and tested at an experimental level to verify its effectiveness in practice. Future work will include optimization of depth penetration, bandwidth, and incorporation into a multi-element imaging system for diagnostic applications.